Lymphocyte apoptosis in children with central nervous system tuberculosis: a case control study - Carlo Paola Di; Casuccio Alessandra; Romano Amelia; Spicola Daria; Titone Lucina; Caccamo Nadia; Dieli Francesco; Mammina Caterina; Pace Elisabetta; Gjomarkaj Mark; Melis Mario; Tolomeo Manlio (BMC, 2011)
Abstract Background Studies of the apoptosis mechanisms involved in the pathogenesis of tuberculosis have suggested that Mycobacterium tuberculosis can actively interfere with the apoptosis of infected cells. In vivo studies have been performed in adult populations but have not focused on this process in children. In the present study, we analyzed spontaneous T lymphocyte (PBT) apoptosis in the peripheral blood of children with central nervous system tuberculosis (CNS TB), before and after chemotherapy, and compared the results with healthy controls. Methods A case-control study was conducted from January 2002 to June 2009. It included 18 children with CNS TB and 17 healthy controls. Spontaneous apoptosis of PBTs, including CD4+, CD8+ and CD8+/CD28+ T cells, was evaluated after 24 and 72 h of culture in complete medium, using the Annexin V detection test. Analysis was conducted before and after chemotherapy, and expression of the apoptotic markers CD95 (Fas) and Fas ligand (FasL) was evaluated. Results Higher percentages of apoptotic T cells and CD4 lymphocytes were isolated from children with acute phase CNS TB than from children in the control group (p < 0.05). This difference significantly decreased after 60 days of specific treatment. In children with CNS TB, high levels of Fas ligand expression were detected in lymphocyte populations, associated with a high percentage of Fas positive cells, before and after treatment. In contrast to the CD4+ apoptosis profile, we did not find any significant difference in total CD8+ cell apoptosis between children with acute phase disease and the control group. However, the percentage of apoptotic CD8+/CD28+ T cells was significantly higher in the children with acute phase disease than in the healthy controls. Conclusions Our findings indicate that CNS TB in pediatric patients increases the sensitivity of CD4 and CD8+/CD28+ T cells to apoptosis, suggesting a hypoergic status of this infection. This could play a key role in the immunopathogenesis of this complicated form of TB. Interestingly, specific chemotherapy is able to normalize both apoptosis sensitivity and T-cell activation.